APPLICATION OF THE SYSTEM ANALYSIS OF IMPLEMENTATION OF THE INSTRUMENTAL METHOD OF NAVIGATION ON INLAND WATERWAYS OF UKRAINE - Panin, V. V.; Doronin, V. V.; Aleynikov, V. M. (Radio Electronics, Computer Science, Control, 2018)
Context. The task of applying the scientific approach to the introduction of a modern navigation system on inland waterways of Ukraine is considered to solve, first of all, weakly structured problems characterized by the presence of an uncertainty factor and containing both formalized and unformulated elements that are not translated into the language of mathematics. Objective – development of the methodology of system analysis at the stage of introduction of the instrumental method of navigation on inland waterways of Ukraine, which guarantees high quality of modeling in accordance with the exact criteria of navigation and economy. Method. An approach to data processing is proposed, which is based on the study of the properties of the system with her further formalization. A model of the layout of the system based on electronic chart systems is developed, characterizing the fulfillment of the assigned tasks with an increased probability of safe navigation. The features of the state of the system using a mathematical model in the form of an undirected graph are considered. An algorithm for realizing the functional stability of the system is proposed. The results of the experiments make it possible to recommend the proposed method for introducing the instrumental method of navigation on inland waterways of Ukraine. Results. The parameters of experimental research of the functioning of the stages of the functional stability of the coastal infrastructure and ship navigation equipment have been developed. Conclusions. In the process of research a set of procedures that contain elements of scientific novelty are used and are aimed at formulating a problem situation, proposing a set of alternatives that are compared with performance criteria using the system stability factors.